2013
DOI: 10.1371/journal.pone.0054966
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy to Produce a Defensin: Stable Production of Mutated NP-1 in Nitrate Reductase-Deficient Chlorella ellipsoidea

Abstract: Defensins are small cationic peptides that could be used as the potential substitute for antibiotics. However, there is no efficient method for producing defensins. In this study, we developed a new strategy to produce defensin in nitrate reductase (NR)-deficient C. ellipsoidea (nrm-4). We constructed a plant expression vector carrying mutated NP-1 gene (mNP-1), a mature α-defensin NP-1 gene from rabbit with an additional initiator codon in the 5′-terminus, in which the selection markers were NptII and NR gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…Microalgae including Chlorella sp. (Trebouxiophyceae) [14,15], Dunaliella salina (Chlorophyceae) [16], Nannochloropsis oculata (Eustigmatophyceae) [17,18] and the diatom Phaeodactylum tricornutum (Bacillariophyceae) [19] have been reported to successfully express biopharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae including Chlorella sp. (Trebouxiophyceae) [14,15], Dunaliella salina (Chlorophyceae) [16], Nannochloropsis oculata (Eustigmatophyceae) [17,18] and the diatom Phaeodactylum tricornutum (Bacillariophyceae) [19] have been reported to successfully express biopharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the biologically active defensin was examined by means of in vitro antimicrobial tests. Afterward, the same research group reported to have successfully obtained stable cell lines of transformed C. ellipsoidea expressing bioactive defensin . The recombinant defensin was claimed to be as high as 11.42 mg/L even after 15 generations.…”
Section: Current Claims Of Heterologous Proteins In Chlorella Subspeciesmentioning
confidence: 99%
“…Although the commercial production of heterologous proteins by Chlorella is currently unachievable, several studies that utilized engineered Chlorella to express heterologous proteins provide much promise (Table ). Various studies have reported that the yields of heterologous proteins by Chlorella vary from 200 ng/L to 11.42 mg/L , which is relatively lower than that for other eukaryotic expression hosts, such as plants (0.1 μg/L to 247 mg/L) , mammalian cells (0.55 to 80 mg/L) , and insect cells (80 to 300 mg/L) . However, low protein yields can be compensated by the short cycle time (typically several days) because of the rapid growth of Chlorella .…”
Section: Current Claims Of Heterologous Proteins In Chlorella Subspeciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformation of C. ellipsoidea C. ellipsoidea was transformed according to a previously published method [39]. Briefly, cells were cultured to the logarithmic phase in Endo medium (10 mL, containing approximately 10 7 cells/mL), collected by centrifugation and resuspended in 10 mL of a solution of 0.2 M mannitol and 0.2 M sorbitol (Sigma Aldrich, St. Louis, United States).…”
Section: Construction Of the Gmdof4 Plant Expression Vectormentioning
confidence: 99%